The reality and prospects of investing in renewable energies - with reference to the case of Algeria - - Khouloufi, Ouahiba (Journal of Human Sciences, 2021)
There is increasing interest in studying the subject of renewable energies, as they represent one of the main sources of global energy outside conventional energy, as well as being clean and non-polluting. This is what we will try to highlight through this study by shedding light on the reality of investing in renewable energies in the world and the Arab world, and a special reference to the case of Algeria.The study found that there are significant investments in renewable energies in the world, especially in the major countries. As for Algeria, it is still making considerable efforts to encourage investment in renewable energies and seeks to exploit the abundant natural resources in this field.